Hubungan Fungsi Keluarga dan Peran Teman Sebaya dengan Perilaku Bullying pada Remaja di SMAN 5 Depok: Relationship of Family Functions and Role of Peer with Bullying Behavior in Teenagers at SMAN 5 Depok - Ratnawati, Diah (Stikes Wira Medika Bali, 2020)
The phenomenon of bullying within adolescents has reemerge to the center of public attention. Bullying is abuse of power that is always carried out by a child or a group of child to injure feelings or to distress. This research purpose is to determine the relationship between family function and role of peers with bullying in teenagers at SMAN 5 Depok. This Research uses the Chi-Square test with a descriptive approach of cross-sectional analytic. Total samples are 167 teenagers, and was carried out using a Stratified random sampling technique. The results of the study obtained a positive relationship between family function and bullying behavior in teenagers in SMAN 5 Depok with a p-value 0.030 with OR = 2.078. This means that the function of family had a chance of 2.078 times to positively conduct bullying behavior. While there is a positive relationship between peer roles and bullying behavior in teenagers with p-value = 0.008 with OR = 2.430. This means the role of poor peers is 2.430 times to positively conduct bullying behavior. Researchers advise teenagers to better appreciate their peers, by not hurting or ridiculing other friends and avoiding physical, psychological, verbal and cyberbullying forms.